SERPINA1 gene identified in RNA-Seq showed strong association with milk protein concentration in Chinese Holstein cows - Li, Cong (PeerJ, 2020)
The detection of candidate genes and mutations associated with phenotypic traits is important for livestock animals. A previous RNA-Seq study revealed that SERPINA1 gene was a functional candidate that may affect milk protein concentration in dairy cows. To further confirm the genetic effect of SERPINA1 on milk protein traits, genetic polymorphisms were identified and genotype-phenotype associations were performed in a large Chinese Holstein cattle population. The entire coding region and the 5′-regulatory region (5′-UTR) of SERPINA1 was sequenced using pooled DNA of 17 unrelated sires. Association studies for five milk production traits were performed using a mixed model with a population encompassing 1,027 Chinese Holstein cows. A total of four SNPs were identified in SERPINA1, among which rs210222822 and rs41257068 presented in exons, rs207601878 presented in an intron, and rs208607693 was in the 5′-UTR. Analyses of pairwise D′ measures of linkage disequilibrium (LD) showed strong linkage among these four SNPs (D′ = 0.99–1.00), and a 9 Kb haplotype block involving three main haplotypes with GTGT, CCCC and CCGT was inferred. An association study revealed that all four single SNPs and their haplotypes had significant genetic effects on milk protein percentage, milk protein yield and milk yield (P = 0.0458 −  < 0.0001). The phenotypic variance ratio for all 11 significant SNP-trait pairs ranged from 1.01% to 7.54%. The candidate gene of SERPINA1 revealed by our previous RNA-Seq study was confirmed to have pronounced effect on milk protein traits on a genome level. Two SNPs (rs208607693 and rs210222822) presented phenotypic variances of approximately 7% and may be used as key or potential markers to assist selection for new lines of cows with high protein concentration.